In situ spawning in a marine broadcast spawner, the Pacific oyster Crassostrea gigas: Timing and environmental triggers. (8th February 2016) - Bernard, I.; Massabuau, J.‐C.; Ciret, P.; Sow, M.; Sottolichio, A.; Pouvreau, S.; Tran, D.
Abstract: The precise environmental conditions under which broadcast spawners spawn in the field remain largely unknown. We investigated this issue in the oyster Crassostrea gigas using three different methods at different time scales in two traditional oyster farming areas of the French Atlantic Coast, the Bay of Arcachon and Marennes‐Oléron. We directly recorded spawning at high temporal resolution using high‐frequency non‐invasive (HFNI) valvometry from 2007–2014 and measured the dry mass and oyster larvae abundance in 2008 and 2009. We analyzed a 29‐yr series of oyster D‐larvae numbers in the Bay of Arcachon (1982–2010). By combining these three approaches, we demonstrated that during the summer months at both sites, spawning in C. gigas occurs in the morning or during the evening, essentially at high tide of perigean spring tides, independent of the positions of these oysters, above or below the lowest water level. We characterized the associated water currents at the spawning location in the Bay of Arcachon and observed that spawning systematically occurs during the early phase of a water current peak, at the beginning of ebbing. We propose that this water current peak acts as a final trigger for spawning. These results have ecological consequences associated with gamete encounters and the dispersal of fertilized eggs (zygotes).